2019
DOI: 10.1001/jamaneurol.2019.1464
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cortical Stimulation–Induced Seizure With Surgical Outcome in Patients With Focal Drug-Resistant Epilepsy

Abstract: IMPORTANCE Cortical stimulation is used during presurgical epilepsy evaluation for functional mapping and for defining the cortical area responsible for seizure generation. Despite wide use of cortical stimulation, the association between cortical stimulation-induced seizures and surgical outcome remains unknown.OBJECTIVE To assess whether removal of the seizure-onset zone resulting from cortical stimulation is associated with a good surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 33 publications
2
80
1
Order By: Relevance
“…A final difference is that bedside stimulation mapping was performed in >70% of the SDE cases, but in the minority of SEEG cases, which may reflect in part an institutional bias and comfort with eloquent cortex mapping utilizing SDEs. However, we found stimulation‐induced seizures occurred over twice as frequently in the SEEG patients, similar to a recent study 42 . This observed difference may be explained by intrinsic biologic differences in excitability of the epileptic networks, electrode anatomic locations, variations in charge density applied between electrode types, rationale for mapping, or a combination of these and other factors 43 …”
Section: Discussionsupporting
confidence: 88%
“…A final difference is that bedside stimulation mapping was performed in >70% of the SDE cases, but in the minority of SEEG cases, which may reflect in part an institutional bias and comfort with eloquent cortex mapping utilizing SDEs. However, we found stimulation‐induced seizures occurred over twice as frequently in the SEEG patients, similar to a recent study 42 . This observed difference may be explained by intrinsic biologic differences in excitability of the epileptic networks, electrode anatomic locations, variations in charge density applied between electrode types, rationale for mapping, or a combination of these and other factors 43 …”
Section: Discussionsupporting
confidence: 88%
“…Whether clinical signs occurred earlier during DCS-S than during SS was not evaluated, a finding that seems frequent in DCS-S presenting with initial motor semiology. 41 In a second SEEG series where 59 (57%)/103 patients had at least one electroclinical DCS-S, 42 the groups of Montreal and Grenoble showed that the use of 50 Hz DCS and longer time (>24 hours) since the last seizure was associated with a higher likelihood of seizure elicitation ( P < .05). More importantly, they demonstrated that the percentage of patients with DCS-S was higher in the good (Engel class I) versus the poor (class II-III-IV) surgical outcome group (70% vs 47%, P = .020), and that the median percentage of the resected contacts encompassing the DCS-induced seizure-onset zone was higher in the good (63%) versus the poor (33%) surgical outcome group ( P = .003).…”
Section: Identifying the Seizure Onset Zone And The Size Of The Resecmentioning
confidence: 97%
“…To date, few studies have directly correlated the use of SEEG ESM with surgical outcomes as measured using the Engel classification system. However, more studies have investigated the ability of stimulation to induce electro-clinical seizures matching the (37). Another study of patients with polymicrogyria (PMG) showed that, while only partial PMG-EZ concordance was found in 74% of cases, subsequent surgery resulted in a favorable outcome in 72% of patients (Engel class I at mean 4.6-year follow-up) (38).…”
Section: Primary Clinical Outcome Metrics Derived From Seeg Stimulatimentioning
confidence: 99%